Systemic absorption of antioxidants from mulberry (Morus alba L) leaf extracts using an in situ rat intestinal preparation - Lee, C.Y.; Sim, S.M.; Cheng, H.M. (2007)
Consumption of antioxidant-rich foods is thought to be capable of increasing our body antioxidant levels, but little is known about their systemic bioavailability. The aim of this study was to demonstrate the systemic absorption of antioxidants from the aqueous and ethanol extracts of mulberry leaves by using an in situ rat intestinal preparation. After an overnight fast, the carotid artery of an anesthetized rat was cannulated, followed by isolation of a short length (8-13 cm) of the duodenum, jejunum, or ileum. Blood samples were collected from the artery before and at various times after administration of the extract or vehicle into the isolated intestinal segment. The collected plasma samples were assayed for their total antioxidant activity (TAA). There was a transient increase in the plasma TAA for animals given the aqueous extract at the ileum, but not when given at the duodenum or jejunum. This suggests that the water-extracted antioxidants need to be hydrolyzed, probably by bacteria, before absorption. For animals given the ethanol extract, significant increase in the plasma TAA occurred at different times for duodenal, jejunal, and ileal segments. This indicates that the ethanol-extracted antioxidants are more readily absorbed. The absorption of these antioxidants probably involves several different mechanisms, and may be influenced by the vehicle of administration. In conclusion, the antioxidants in mulberry leaves are absorbed to different extents throughout the small intestine of rats. Furthermore, this in situ preparation may be used to screen for systemic bioavailability of antioxidants in herbal samples. (c) 2007 Elsevier Inc. All rights reserved.